ANALISIS PARTISIPASI MASYARAKAT LOKAL DALAM PENGEMBANGAN WISATA RAFTING DI KABUPATEN BOGOR - Wiwik Nirmala Sari (Magister Tourism Study, Faculty of Tourism, Udayana University, 2023)
This research aims to know the participation of local communities in the development of Cisadane River rafting tourism, Bogor Regency. This research includes qualitative research, using the methods of observation, literature study, documentation and interviews to collect data. Several informants were determined using a purposive sampling technique in which the informants were selected based on certain considerations. The collected data were analyzed by means of descriptive analysis. The results showed that the form of local community participation in the development of rafting tourism, Cisadane River, Bogor Regency, was not optimal. Community participation is only in the form of participation in the implementation of rafting tourism and taking benefits, not in decision making and activity evaluation. It is hoped that in the future the development of rafting tourism around the Cisadane River, Bogor Regency can involve the community optimally, starting from decision making, implementation, taking benefits, and the evaluation of development. Optimal community participation can increase the sense of belonging and responsibility for the community, so that the sustainability of rafting tourism can be guaranteed. Keywords: participation; local community; rafting tourism; tourism.